Remote sensing quantifies widespread abundance of permafrost region disturbances across the Arctic and Subarctic - I. Nitze (Nature Portfolio, 2018)
The occurrence and distribution of permafrost region disturbances (PRDs) remain poorly resolved across the Arctic and Subarctic. Here, the authors quantify the abundance and distribution of three primary PRDs using a time-series analysis of 30-m resolution Landsat imagery between 1999 and 2014.